1989
DOI: 10.1021/ac00183a019
|View full text |Cite
|
Sign up to set email alerts
|

On-column capillary flow cell utilizing optical waveguides for chromatographic applications

Abstract: 30) Pace, C. F.; Thornberg, S. M.; Maple, J. R. Appl. Spechosc. 1988, (31) Wiilis, B. G.; Woodruff, W. H.; Frysinger, J. R.; Margerum, D. w.; Par-(32) Meiling, G. E.; Pardue, H. L.The high separatlon efficiencies provided by various chromatographic technlques employlng microbore and capillary columns, countered by current detection llmltatlons, present new challenges In detection cell design. I n thls contrlbution we descrlbe a device sultable for on-column simultaneous absorption and fluorescence detection th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In photometric detection in CE using LEDs it has been shown that it is the stray light (light which reaches the detector without passing through the detection window) that is the key parameter which mostly determines detector linearity, rather than a lack of an ideally monochromatic light source [15]. While a number of approaches can be used to evaluate detector linearity [15,[27][28][29], in this study we followed the approach of Macka et al [15] by measuring the response (absorbance) of a series of standard solutions in order to calculate sensitivity (absorbance/concentration). Sensitivity was then plotted against absorbance to determine the absorbance value at which sensitivity began to decrease from its maximum value.…”
Section: Detector Design and General Considerationsmentioning
confidence: 99%
“…In photometric detection in CE using LEDs it has been shown that it is the stray light (light which reaches the detector without passing through the detection window) that is the key parameter which mostly determines detector linearity, rather than a lack of an ideally monochromatic light source [15]. While a number of approaches can be used to evaluate detector linearity [15,[27][28][29], in this study we followed the approach of Macka et al [15] by measuring the response (absorbance) of a series of standard solutions in order to calculate sensitivity (absorbance/concentration). Sensitivity was then plotted against absorbance to determine the absorbance value at which sensitivity began to decrease from its maximum value.…”
Section: Detector Design and General Considerationsmentioning
confidence: 99%
“…The capillary flow cells with optical fibres were used successfully in liquid-phase separation techniques such as electrophoresis [250] and high-temperature HPLC [251]. Bruno et al [252] developed a capillary flow cell with optical fibres for use in open tubular column SFC. On the basis of a ray tracing algorithm, they formulated the guidelines for selecting proper diameters of the source and the collecting fibres to fit a particular capillary tube.…”
Section: Detectionmentioning
confidence: 99%
“…One problem with the bubble is that different light rays traverse the bubble via very different paths, some with no interaction with the fluid at all, others with an optical interaction length equal to the full inner bubble diameter, to mention only both extremes. Another concept employs U-or Z-cells, where the middle part of the U or of the Z is used as an optical path [4]- [7]. But typically U-or Z-cells have larger inner channel diameters than the capillary itself and are extra parts of the separation column, which have to be physically attached to the capillary somehow.…”
Section: Introductionmentioning
confidence: 99%